Salvage Radiotherapy for Macroscopic Local Recurrence Following Radical Prostatectomy - Zaine, Hind; Vandendorpe, Benjamin; Bataille, Benoit; Lacornerie, Thomas; Wallet, Jennifer; Mirabel, Xavier; Lartigau, Eric; Pasquier, David (Frontiers in Oncology, 2021)
Introduction Salvage radiotherapy is the only curative treatment for biochemical progression after radical prostatectomy. Macroscopic recurrence may be found in the prostatic bed. The purpose of our study is to evaluate the effectiveness of salvage radiotherapy of the prostate bed with a boost to the area of the macroscopic recurrence. Material and Methods From January 2005 to January 2020, 89 patients with macroscopic recurrence in the prostatectomy bed were treated with salvage radiotherapy +/- hormone therapy. The average PSA level prior to radiotherapy was 1.1 ng/mL (SD: 1.6). At the time of biochemical progression, 96% of the patients had a MRI that revealed the macroscopic recurrence, and 58% had an additional choline PET scan. 67.4% of the patients got a boost to the macroscopic nodule, while 32.5% of the patients only underwent radiotherapy of the prostate bed without a boost. The median total dose of radiotherapy was 70 Gy (Min.: 60 – Max.: 74). The most commonly-used regimen was radiotherapy of the prostatectomy bed with a concomitant boost. 48% of the patients were concomitantly treated with hormone therapy. Results After a median follow-up of 53.7 months, 77 patients were alive and 12 had died, of which 4 following metastatic progression. The 5-year and 8-year survival rates (CI95%) are, respectively, 90.2% (78.9-95.6%) and 69.8% (46.4-84.4%). The 5-year biochemical progression-free survival rate (CI95%) is 50.8% (36.7-63.3). Metastatic recurrence occurred in 11.2% of the patients. We did not find any statistically significant impact from the various known prognostic factors for biochemical progression-free survival. No toxicity with a grade of > or = to 3 was found. Conclusions Our series is one of the largest published to date. Salvage radiotherapy has its place in the management of patients with biochemical progression with local recurrence in the prostate bed, with an acceptable toxicity profile. The interest of the boost is to be evaluated in prospective trials.